Hemolytic-uremic syndrome: 24 years’ experience of a pediatric nephrology unit - Vilardouro,Ana Sofia (2022)
Abstract Introduction: A better understanding of hemolytic-uremic syndrome (HUS) pathophysiology significantly changed its treatment and prognosis. The aim of this study is to characterize the clinical features, severity, management, and outcomes of HUS patients. Materials and Methods: Retrospective study of HUS patients admitted to a Pediatric Nephrology Unit between 1996 and 2020. Demographic and clinical data regarding etiology, severity, treatment strategies, and patient outcome were collected. Results: Twenty-nine patients with HUS were admitted to our unit, but four were excluded. Median age at diagnosis was two years (2 months - 17 years). Clinical manifestations included diarrhea, vomiting, oliguria, hypertension, and fever. During the acute phase, 14 patients (56%) required renal replacement therapy. Infectious etiology was identified in seven patients (five Escherichia coli and two Streptococcus pneumoniae). Since 2015, 2/7 patients were diagnosed with complement pathway dysregulation HUS and there were no cases of infectious etiology detected. Six of these patients received eculizumab. The global median follow-up was 6.5 years [3 months-19.8 years]. One patient died, seven had chronic kidney disease, four of whom underwent kidney transplantation, one relapsed, and seven had no sequelae. Conclusion: These results reflect the lack of infectious outbreaks in Portugal and the improvement on etiological identification since genetic testing was introduced. The majority of patients developed sequels and mortality was similar to that of other countries. HUS patients should be managed in centers with intensive care and pediatric nephrology with capacity for diagnosis, etiological investigation, and adequate treatment. Long-term follow-up is essential.